PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BADAN PUSAT STATISTIK (BPS) KOTA PADANG - Saputra, Andri; Natassia, Rizky; Amaluis, Dina (Pendidikan Ekonomi, 2013)
ABSTRACT Andri Saputra , NPM : 09,090,003. Effects of Leadership Styles and Work Motivation on Employee Performances Statistics Agency (BPS) of Padang. Main supervisor : Rizky Natassia, SE , MM and Second Supervisor : Dina Amaluis , SE , MM.This study aims to reveal the influence of leadership style on employee motivation Central Statistics Agency ( BPS ) of Padang , the influence of leadership styles on employee performance Central Statistics Agency ( BPS ) of Padang , the influence of work motivation on employee performance Central Statistics Agency ( BPS ) Padang , the influence of leadership style and employee motivation Central Statistics Agency ( BPS ) of Padang.Type of research is descriptive research Associative. The population in this study was the overall employees of the Central Statistics Agency BPS ) Padang totaling 30 employees . Sampling technique using Total Sampling amounts 30 employees. Data were collected through a questionnaire using a Likert scale measuring devices that have been tested errors and reliability in the Central Bureau of Statistics ( BPS ) of West Sumatra Province . The data analysis technique used is the Path Analysis (Path Analysis).The results of this study are : there is a positive and significant effect between leadership styles on employee motivation Central Statistics Agency ( BPS ) Padang , there is a positive and significant effect between leadership styles on employee performance Central Statistics Agency ( BPS ) Padang , there positive and significant influence between work motivation on employee performance Central Statistics Agency ( BPS ) Padang , there is a positive and significant effect between leadership style and work motivation on employee performance Central Statistics Agency ( BPS ) of Padang . Total direct and indirect effects of leadership style variable and employee motivation is at 36 % while the remaining 64 % is influenced by other variables.From the analysis of the data in this study , the authors suggested that the leadership of the Central Statistics Agency ( BPS ) Padang further enhance and apply leadership style in order to better motivate employees who are owned by the Central Statistics Agency ( BPS ) Padang be increased as well . The author suggests that the leadership of the Central Statistics Agency (BPS) Padang further enhance and apply leadership style as well as provide motivation to employees so that employee performance can be increased also for the progress of the organization. Keywords: Leadership Style, Work Motivation, Performance, and Path Analysis